Electrochemical Biosensors as Potential Diagnostic Devices for Autoimmune Diseases - Florea, Anca (Biosensors (Basel), 2019)
An important class of biosensors is immunosensors, affinity biosensors that are based on the specific interaction between antibodies and antigens. They are classified in four classes based on the type of employed transducer: electrochemical, optical, microgravimetric, and thermometric and depending on the type of recognition elements, antibodies, aptamers, microRNAs and recently peptides are integrating parts. Those analytical devices are able to detect peptides, antibodies and proteins in various sample matrices, without many steps of sample pretreatment. Their high sensitivity, low cost and the easy integration in point of care devices assuring portability are attracting features that justify the increasing interest in their development. The use of nanomaterials, simultaneous multianalyte detection and integration on platforms to form point-of-care devices are promising tools that can be used in clinical analysis for early diagnosis and therapy monitoring in several pathologies. Taking into account the growing incidence of autoimmune disease and the importance of early diagnosis, electrochemical biosensors could represent a viable alternative to currently used diagnosis methods. Some relevant examples of electrochemical assays for autoimmune disease diagnosis developed in the last several years based on antigens, antibodies and peptides as receptors were gathered and will be discussed further.